Etiology and Survival of Secondary Revascularizations after Hand and Digit Replantations - Shaterian, Ashkaun; Sayadi, Lohrasb Ross; Anderson, Amanda; Santos, Pauline J. F.; Ng, Wendy K. Y.; Evans, Gregory R. D.; Leis, Amber (Journal of Hand and Microsurgery, 2020)
Introduction Hand and digit replantations can be complicated by vascular insufficiency necessitating revision of the original replantation. To date, few studies have evaluated outcomes in secondary revascularizations following replantation. Therefore, the objective of this study was to evaluate the incidence, etiology, and survival rates following secondary revascularization after hand and digit replantations.Materials and Methods A literature search was performed on NCBI for studies documenting secondary revascularization procedures following hand and digit replant. Studies were evaluated for the etiology of vascular failure, frequency of secondary revascularization, and survival rates following intervention. Statistical analysis was conducted across the pooled dataset.Results A total of 16 studies including 1,192 amputations were analyzed. We found that 16.9% (201/1,192) of replants were complicated by vascular compromise. The frequency of vascular compromise was not statistically different between arterial and venous etiologies. The survival rate following secondary revascularization was 55.6%, with no significant difference between the arterial and venous groups. Secondary arterial revascularization was often treated with arterial revision (nine of nine studies) and/or with vein grafting (two of nine studies). Secondary revascularization for venous insufficiency resulted in different survival rates for nonsurgical modalities (58%) versus vein revision (37.5%) versus vein grafting (100%).Conclusion Survival rates following secondary revascularization are lower; however, they may be improved using vein grafts following venous insufficiency. These data can be used to better understand the etiology of replant failure and guide decision-making.
Keywords: amputation; replantation; revascularization; digit; hand